The incidence of congenital heart defects in the world regarding the severity of the defect - Miranović Vesna (Vojnosanitetski Pregled)
Bacground/Aim. Congenital heart defects (CHDs) are structural or functional abnormalities of the heart present at birth even if they are detected much later. Their importance lies in the fact that, depending on the severity, they change the quality of life, and may be life threating. In addition, we should not ignore the high costs of treating people with congenital heart disease. The aim of this study was to analyze the incidence of congenital heart disease in relation to the severity in the world based on the available literature. Methods. All the available literature on the incidence of CHD cases regarding the severity of CHD published from 1955 to 2012 was analyzed. The researcher was able to read the titles and abstracts of 128 papers on the subject. Due to methodological inconsistency, 117 of the papers were rejected. Based on the criteria of reliability, availability and comparability, our analysis included 11 studies testing CHD incidence regarding the severity of the defect conducted all over the world. The Yates' χ2-test was used to compare the observed incidences. Results. The frequency of severe congenital heart defects, ranged from 0.414 to 2.3/1,000 live births, the incidence of moderate congenital heart defects from 0.43 to 2.6/1,000 live births while in the group of minor congenital heart defects the incidence ranged from 0.99 to 10.3/1000 live births. There were no statistically significant differences in the incidence of mild, moderate and severe CHDs. Conclusion. The results obtained studying of the available data suggest that no statistically significant difference in the incidence of mild, moderate and severe congenital heart defects. A universal methodological approach to the incidence of CHD is essential.